Research on the axial compression performance of coral concrete-filled aluminum alloy tube columns - Jianhua Guo; Yumei Wang; Zhiheng Deng; Ping Chang (Case Studies in Construction Materials, 2024)
The compression of coral concrete-filled aluminum alloy tube columns is a novel type of laterally restrained concrete element, with axial compressive load being the primary load type sustained by the laterally restrained concrete elements during their service life. In this study, square intermediate-length columns of coral concrete-filled aluminum alloy tubes were subjected to axial compression tests to investigate the influence of section width-to-thickness ratio (B/t), and aspect ratio of the column (L/B) on the failure mode, ultimate load-carrying capacity, and load-deformation relationship of the specimens. The research findings demonstrate that the intermediate-length columns of coral concrete-filled aluminum alloy tube exhibit good compressive performance, with a significant combined effect between the aluminum alloy tube and the core concrete. With an increase in the section width-to-thickness ratio (B/t), the compressive stiffness, ultimate load-carrying capacity, and deformation ductility of the specimens all decrease. As the aspect ratio of the column (L/B) increases, under the condition that end-zone failure does not occur, the ultimate load-carrying capacity and deformation ductility of the specimens gradually decrease, while the extent of flexural deformation significantly increases.